Strategi Pemanfaatan Digital Marketing dalam Mengembangkan Desa Wisata Lembah Pinus Surodadi Kabupaten Magelang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The development of the tourism industry in a region can provide positive impacts and values, namely increasing community income, increasing employment opportunities and business fields, increasing regional income from taxes and government-owned business profits and so on. This study aims to analyze development strategies, impacts, and challenges in implementing digital marketing in the Lembah Pinus Tourism Village. The method used in this study is qualitative research with a case study approach and literature review using descriptive analysis methods. This study uses data collection techniques by means of interviews, observations, and documentation are in-depth interviews with tourism managers, local communities, and tourists.The results of the study show that the digital marketing strategy implemented has played an important role in increasing the number of visitors, namely by utilizing social media such as Instagram, TikTok, and WhatsApp, which has proven effective in introducing and promoting this tourism to the wider public. With a total of 1,324 visitors throughout 2023 to 7,771 visitors throughout 2024, the majority of tourists know about the existence of this tourist village from digital platforms. Although the promotion has been going well, there is still potential for improvement through the use of digital analytics tools to measure the effectiveness of marketing promotions more systematically. There are several challenges that must be faced in developing a digital marketing strategy, including consistency in managing social media, limited human resources, suboptimal infrastructure, and fluctuations in the number of visitors. In addition, the uncertainty of the number of tourists means that digital marketing cannot yet be the only source of income for local business actors. These obstacles need further attention so that digital marketing strategies can run more effectively and efficiently.